Evaluation of an educational intervention on HIV/AIDS for adolescent students in Antofagasta, Chile - Marrodán-García, Marco; Álvarez-Giménez, Romina; Muñoz-Tapia, Claudia; Vega-Pizarro, Karina; Véliz-Romero, Katherine (Revista Chilena de Salud Pública, 2018)
Basis: Adolescents are becoming sexually active at an increasingly young age, and risk contracting sexually transmitted diseases such as HIV/AIDS. Between 2009 and 2013, the incidence rate of this illness among 15 to 19 year olds rose by 74.1% in Chile. Studies suggest that modification of sexual behavior through educational initiatives is a means by which young people can be encouraged to avoid risky behavior. The objective of this study is to analyze the impact of an educational intervention about HIV/AIDS on knowledge, sexual behavior, and the tendency to discriminate against individuals with HIV, among 9th grade students from a private, subsidized secondary school in Antofagasta, Chile. Methods: Longitudinal study of 70 adolescents between 14 and 15 years of age. The students were evaluated before and after an educational intervention about HIV/AIDS using a survey designed to measure their knowledge, behavior and attitudes. Results: In terms of knowledge about HIV/AIDS, the number of students obtaining results classed as Very Good and Excellent increased from 17% pre-intervention to 72% after the intervention. Those who correctly identified preventative measures increased from 54% to 78%, and those who claimed that being homosexual or bisexual leads to a greater risk of developing HIV reduced from 36% to 30%. Conclusions: The level of knowledge about HIV/AIDS increased. Preventative sexual behaviors increased in the hypothetical situations presented by the study. With regard to potentially discriminatory attitudes, there was a small decrease.